Equation of state for ε-iron at high pressures and temperatures - Belonoshko, A.B. (Condensed Matter Physics, 2010)
Computations were performed using the facilities at the Swedish National Infrastructure for Computing (SNIC). Financial support from the Swedish Research Council (VR) is gratefully acknowledged.